Panax notoginseng Root Cell Death Caused by the Autotoxic Ginsenoside Rg1 Is Due to Over-Accumulation of ROS, as Revealed by Transcriptomic and Cellular Approaches - Yang, Min; Chuan, Youcong; Guo, Cunwu; Liao, Jingjing; Xu, Yanguo; Mei, Xinyue; Liu, Yixiang; Huang, Huichuan; He, Xiahong; Zhu, Shusheng (Frontiers in Plant Science, 2018)
Panax notoginseng is a highly valuable medicinal herb, but its culture is strongly hindered by replant failure, mainly due to autotoxicity. Deciphering the response mechanisms of plants to autotoxins is critical for overcoming the observed autotoxicity. Here, we elucidated the response of P. notoginseng to the autotoxic ginsenoside Rg1 via transcriptomic and cellular approaches. Cellular analyses demonstrated that Rg1 inhibited root growth by disrupting the cell membrane and wall. Transcriptomic analyses confirmed that genes related to the cell membrane, cell wall decomposition and reactive oxygen species (ROS) metabolism were up-regulated by Rg1 stress. Further cellular analyses revealed that Rg1 induced ROS (O2·- and H2O2) accumulation in root cells by suppressing ascorbate peroxidase (APX) and the activities of enzymes involved in the ascorbate-glutathione (ASC-GSH) cycle. Exogenous antioxidants (ASC and gentiobiose) helped cells scavenge over-accumulated ROS by promoting superoxide dismutase (SOD) activity and the ASC-GSH cycle. Collectively, the autotoxin Rg1 caused root cell death by inducing the over-accumulation of ROS, and the use of exogenous antioxidants could represent a strategy for overcoming autotoxicity.